Impact of ethical leadership on affective commitment through mediating impact of ethical climate: A Conceptual study - Halbusi, Hussam Al; Tehseen, Shehnaz * (Australia, 2018)
The ethical leadership has received attention in recent years due to the various business scandals and ethical issues including corporate leaders. Recently ethical climate has been issued as a vital environmental factor. The main purpose of this study was to develop a conceptual model based on existing studies. The proposed theoretical framework suggests the mediating role of ethical climate in the relationship between ethical leadership and affective commitment. Thus, the ethical climate could act as a mechanism that brings a greater affective commitment in the workplace.